Research on urban ecosystem health evaluation of Yunnan Province based on principal component analysis method - Huang, Jinyong; Kang, Linglin (International Journal of Social Sciences and Public Administration, 2023)
Urban ecosystem consists of environment, social culture and economy, and the health of urban ecosystem determines the quality of life of residents and is an important dependence of human life. Through the official statistics of Yunnan Province in the past five years, a number of subdivided indicators of urban data are selected and dimensionality is reduced using principal component analysis to obtain the urban ecosystem health evaluation system, which makes a comprehensive assessment of the health and development of the ecosystems in Yunnan Province and puts forward suggestions for it. The results show that the overall development of urban ecosystem health in Yunnan Province has been steadily improving over the past five years, with a balanced development in all aspects, and that the future management mode should emphasize the coordinated development of the economy and the ecological environment.